Bracing alternatives in tapered frames under wind loads (2009)
The level of risk caused by forces of the nature could be reduced with an appropriate intervention of vulnerability, since such threats cannot be reduced. One of the alternatives to reduce the structural vulnerability of buildings is provide elements, such as bracing, to improve their behavior when they are subjected to forces arising from these threats. The reduction of vulnerability in buildings type warehouse is achieved with elements that help to absorb horizontal forces acting on it, such as bracing and wind bracing. Due to the limited information about the better way to distribute these elements to reach a good configuration of the structure, we present this document, where we will analyze different distributions for the bracing that provides the best cost-benefit.